Producción de carbón y su efecto socioeconómico-ecológico en las comunidades de San Pedro y nuevo paraíso, río Manatí. Indiana. 2020 - Ramos Navarro, Carlos Paolo (2021)
The subject under study was called “Coal production and its socioeconomicecological effect in the communities of San Pedro and Nuevo Paraíso, Manatí River. Indiana. 2020”. The objective was "Determine the production of charcoal in the San Pedro and Nuevo Paraíso communities, Manatí River, and its socioeconomicecological relationship in the study area." The non-experimental, quantitative, crosssectional research design was used. With a simple probabilistic sample, where 32 people who live in the communities of the study were selected. The results obtained from the surveys were interpreted through descriptive statistics. The variables evaluated were: carbon production, ecological effect, socioeconomic effect. It is concluded that the production of artisanal charcoal influences socioeconomicecological aspects of the study communities, be they positive and negative aspects. In the ecological aspect, positive aspects are rescued: they do not constantly change places to burn the woodpile (68.75%) in addition to extracting the forest species from their own plots. It negatively affects the loss of tree biodiversity and alteration of the alluvial landscape. Regarding the socioeconomic aspect, they generate economic income that helps alleviate the economy of the producer, and because of the roots of maintaining their land in these areas. Family labor prevails in all coal production activities that save costs, but for which production is not higher. It does not require a lot of capital to develop this activity, but since they do not have an organization of producers, many of them see their income from sales to intermediary merchants that swarm around the study area minimized.